Divulgação científica no ensino de biologia: uma sequência de ensino com construção de podcast - Matheus Wilhen de Oliveira Glicério (2022)
The complexity of teaching-learning makes preponderant the need to search for new teaching methodologies and methods, in order to enable new (inter)connections between content and learner´s reality. New tools are always emerging and being reinvented such as audio programs, in particular, podcasts. The objective of this research was to use science popularization as a way to facilitate the processe of teaching-learning of genetics and contribute to the teachers’ continuing education enabling them to use digital tools and DTICs for the construction and use of podcasts in science and biology teaching. A teaching sequence was built with multimodal scientific divulgation materials. The sequence evaluation was done through a training workshop for teachers that served to produce podcasts and discussions to improve the sequence. The data collection was done by the observation of the workshops and two electronic questionnaires. Despite being a known media by the participants, none of them had used podcasts as a teaching-learning tool with their students. At the end of the workshop, the teachers considered the methodology as possible and desirable to be used in elementary and high schools. The evaluation of the didactic sequence progressed to a collaborative development of the didactic material with modifications done based on suggestions from the teachers involved and did not imply in changes that would preclude the original sequence; on the contrary, it has made it more solid. As research products we have 1) The final teaching sequence with the theme genetic inheritance made up of multimodal materials, with science popularization texts; 2) a booklet about building podcasts; 3) workshop slides that can be used as a reference or replication model for other teachers; 4) a site in which all these products will be available. The range of products developed from this research can help teachers to encourage students’ protagonism in the development of their knowledge through the construction of scientific podcasts.